2022
DOI: 10.1007/s00223-021-00939-9
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Liver Index and Skeletal Muscle Density

Abstract: Accumulation of fat in the liver and skeletal muscle is associated with obesity and poor health outcomes. Liver steatosis is a characteristic of non-alcoholic fatty liver disease (NAFLD) and myosteatosis, of poor muscle quality in sarcopenia. In this study of 403 men (33–96 years), we investigated associations between the fatty liver index (FLI) and muscle density, as markers of fat accumulation in these organs. We also investigated associations between the FLI and parameters of sarcopenia, including DXA-deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Obesity has numerous detrimental systemic effects on the body, contributing to the development of the metabolic syndrome, including type 2 diabetes mellitus (T2DM), Alzheimer’s disease, various types of cancer, and cardiovascular diseases. Along with these systemic effects, fat accumulation in vital organs such as the liver (hepatic steatosis), skeletal muscle (myosteatosis), and heart (obesity cardiomyopathy) can adversely impact its respective tissue and lead to poor health outcomes [ 28 ]. Notably, an inverse correlation between fatty liver index and muscle density was reported in a population-based prospective cohort study of both male and female subjects [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Obesity has numerous detrimental systemic effects on the body, contributing to the development of the metabolic syndrome, including type 2 diabetes mellitus (T2DM), Alzheimer’s disease, various types of cancer, and cardiovascular diseases. Along with these systemic effects, fat accumulation in vital organs such as the liver (hepatic steatosis), skeletal muscle (myosteatosis), and heart (obesity cardiomyopathy) can adversely impact its respective tissue and lead to poor health outcomes [ 28 ]. Notably, an inverse correlation between fatty liver index and muscle density was reported in a population-based prospective cohort study of both male and female subjects [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Future studies may also consider a more comprehensive assessment of body composition, including muscle adiposity, as there is evidence that individuals with high muscle fat are more likely to have higher liver fat. 49 …”
Section: Discussionmentioning
confidence: 99%
“…Given most previous studies report liver fat as the primary outcome, capacity for more meaningful comparison between other PRT-related studies was also limited. Future studies may also consider a more comprehensive assessment of body composition, including muscle adiposity, as there is evidence that individuals with high muscle fat are more likely to have higher liver fat 49…”
Section: Discussionmentioning
confidence: 99%
“…Additional cross-sectional and retrospective studies have further confirmed the independent association between sarcopenia and NAFLD [ 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ], NAFLD severity [ 35 , 37 , 43 ], fibrosis [ 36 , 40 , 44 , 45 , 46 , 47 ] and fibrosis severity [ 36 , 48 , 49 ].…”
Section: Sarcopeniamentioning
confidence: 95%